Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1021/acscatal.1c04086
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Zeolitic Ti, Zr-Substituted Vanadotungstates and Investigation of Their Catalytic Activities for Low Temperature NH3-SCR

Abstract: Microporous vanadotungstate (W 4 V 3 O 19 , VT-1) was constructed via the connection of [W 4 O 16 ] 8− cubane units with VO 2+ linkers to form an LTA-zeolite-type crystal structure. We found that the VO 2+ sites connecting the cubane units of VT-1 could be partially removed by an appropriate acid treatment without destroying its crystal structure. This process involved a redox reaction between the [W 4 O 16 ] 8− cubane units and VO 2+ linkers, and V was removed as V 5+ during the acid treatment. TiO 2+ or ZrO … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…The chemical formulae of Cu-VT-1 , Zn-VT-1 , and Mn-VT-1 were estimated to be Cu­[W 4 V 3 O 19 ], H 1.4 Zn 1 [W 4 Zn 0.7 V 2.3 O 19 ], and Mn 1.3 [W 4 V 3 O 19.3 ], respectively. For Zn-VT-1 , Zn might also be replaced with some V, which was also observed when using Ti and Zr ions for ion exchange . NH 4 + exchange was carried out for Zn-VT-1 (see the Supporting Information for details), and the structure did not change (Figure S6).…”
Section: Results and Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…The chemical formulae of Cu-VT-1 , Zn-VT-1 , and Mn-VT-1 were estimated to be Cu­[W 4 V 3 O 19 ], H 1.4 Zn 1 [W 4 Zn 0.7 V 2.3 O 19 ], and Mn 1.3 [W 4 V 3 O 19.3 ], respectively. For Zn-VT-1 , Zn might also be replaced with some V, which was also observed when using Ti and Zr ions for ion exchange . NH 4 + exchange was carried out for Zn-VT-1 (see the Supporting Information for details), and the structure did not change (Figure S6).…”
Section: Results and Discussionmentioning
confidence: 90%
“…For Zn-VT-1, Zn might also be replaced with some V, which was also observed when using Ti and Zr ions for ion exchange. 43 NH 4 + exchange was carried out for Zn-VT-1 (see the Supporting Information for details), and the structure did not change (Figure S6). The elemental analysis of the resulting material showed that Zn still existed in the material (Zn content of 1.31%) after NH 4 + exchange, indicating that some Zn 2+ was incorporated into the framework.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…At that time, the O–H distance between NH 4 + and CO 2 was reasonable and was 2.53–2.78 Å after the geometry optimization, and the adsorption energy of E CO2 = −62 kJ mol –1 CO2 was obtained (Figure d). There are a few examples of microporous materials composed of transition-metal elements in an all-inorganic manner. These properties could offer versatile applications due to the microporous structure and redox properties.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Recently, a new class of microporous materials composed of d-block elements, namely, zeolitic octahedral metal oxides (ZOMOs), has been reported, and applications derived from their redox-active constituents and microporosity are being developed. However, ZOMOs are still rare, although much effort has been devoted to their synthesis. …”
Section: Introductionmentioning
confidence: 99%
“…26 Crystalline microporous transition metal oxides composed of metal-oxygen octahedra are assembled by metal oxygen clusters as building units and metal ions as linkers, and therefore the materials are also called zeolitic octahedral metal oxides (ZOMOs). [27][28][29][30] Various ZOMOs have been reported in recent years, such as pentagon unit-based vanadomolydates, [31][32][33][34] hexagonal unit-based cobalt selenotungstate, 35 cubane unit-based vanadotangstate, 30,36,37 and ε-Keggin polyoxometalate (POM) unit-based molybdates. 29,38,39 Among these ZOMOs, the ε-Keggin unit-based molybdates (Fig.…”
Section: Introductionmentioning
confidence: 99%